Quantifying the training demands of a highly trained male youth basketball players by year, term and position - Lever, J. R.; Duffield, R.; Murray, A.; Bartlett, J. D.; Fullagar, H. H. (Journal of Sports Sciences, 2024)
This study describes the training demands of highly trained male youth basketball players, based on training year, term and playing position. Data was collected from 41 male youth basketballers over two seasons from all on-court coach-led training sessions utilising an LPS. Linear mixed-models and pairwise comparisons were used to analyse by training year (Y1, Y2 and Y3), term (T1, T2, T3 and T4) and playing position (Backcourt, Frontcourt). Results showed no differences in external load metrics between training years. Significant differences existed between training terms, with total distance greater in both T3 and T4 than T1 and 2 (p < 0.03). Total PlayerLoad was significantly greater in T4 than T1 (p < 0.001) and T3 (p = 0.004). Distance/min was greater in T2, T3 and T4 than T1 (p < 0.01). PlayerLoad/min was higher in T4 than T1 and T2 (p < 0.01). Backcourt players showed significantly greater distance/min (p = 0.011), PlayerLoad/min (p = 0.011) and deceleration counts (p < 0.001). Overall, limited year-on-year change existed in external training load metrics (p > 0.05), though volume (p < 0.001) and intensity (p < 0.001) differed between terms. Backcourt players completed higher intensities (p = 0.011) than Frontcourt players. This study provides a description of external loads of training in highly trained youth basketball players assisting coaches and performance practitioners to better understand physical demands within youth basketball development pathways.